Double Chamber of Right Ventricle (DCRV) - A Case Report - Rahim, AMA; Hasan, KA; Hasan, MK; Mamun, MMAA; Salam, ABMA; Arif, MA; Mahmood, KN (Cardiovascular Journal, 2011)
Primarily double chamber of Right ventricle (DCRV) is an uncommon congenital anomaly consists of one or more anomalous muscle bundles(AMB) that divide Right ventricle into proximal high and distal low pressure chamber .Outcome of surgical treatment is excellent if diagnosed properly. A 5years old girl presented with breathlessness on exertion and repeated attack of cough, fever for last 4 years .patient ultimately diagnosed as DCRVand underwent intracardiac repair by open heart surgery. Her postoperative outcome was uneventful. Patient is discharged on 8th postoperative day after follow up postoperative chest X Ray and Echocardiography . Keywords: Double chamber of Right ventricle; intracardiac repair DOI: http://dx.doi.org/10.3329/cardio.v3i2.9194 Cardiovasc. J. 2011; 3(2): 226-229